Perturbing the Normal Level of SIDT1 Suppresses the Naked ASO Effect. (16th November 2021) - Takahashi, Masayuki; Seki, Mineaki; Nashimoto, Masayuki; Kabuta, Tomohiro
Abstract : Although antisense oligonucleotide (ASO) therapeutics can be taken up by living cells without carrier molecules, a large part of incorporated ASOs are trapped in the endosomes and do not exert therapeutic effects. To improve their therapeutic effects, it would be important to elucidate the mechanism of cellular uptake and intracellular trafficking of ASOs. In this study, we investigated how SIDT1 affects cellular uptake and intracellular trafficking of ASOs. Fluorescence microscopic analysis suggested that most of naked ASOs are trafficked to the lysosomes via the endosomes. The data obtained from flow cytometry and fluorescence microscopy together showed that although the SIDT1 level barely affects the total cellular uptake of ASOs, it appears to affect the intracellular trafficking of ASOs. We also showed that SIDT1 exists mainly in the endoplasmic reticulum and that perturbing the normal level of SIDT1 suppresses the antisense effect of the naked ASO targeting miR-16.